(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
We investigate the possibility to enhance the atomic fluorescence and using it to measure the ‘second’ by means of a quantum device formed by two-level cold atoms confined in a microwave cavity with harmonically modulated cavity frequency. Besides the harmonically modulated cavity frequency, we have also studied the modification in the atomic fluorescence due to the addition of the squeezing term in the Hamiltonian of the system. The periodic modulation of cavity frequency give rise to non adiabatic process characterized as two-photon process. It has been observed that the two-photon process can be used as a new handle to enhance the atomic fluorescence which helps in improving the accuracy of the atomic fountain clocks.